PERBANDINGAN PENGARUH AKTIVITAS FISIK DANPENGARUH ASUPAN NATRIUM TERHADAP TEKANAN DARAH MAHASISWA TINGKAT I ANGKATAN 2018 FK UPN"VETERAN" JAKARTA - Rahayu Novianti, (2019)
Sodium is the main cation in the body's extracellular fluid which functions in regulating the body's fluid and acid-base balance and plays a role in neural transmission and muscle contraction. Overconsumption of sodium may lead to hypertension. Physical activity is defined as any kind of body movement carried out by skeletal muscle that produces expenditure in a form of calories. Lack of physical activity leads to the increase of heart rate by decreasing parasympathetic nerve tone, an increase in sympathetic nerves which causes an increase in blood pressure. This study was aimed to determine the comparison of the effect of physical activity and the effect of sodium on blood pressure in first-year faculty of medicine students Universitas Pembangunan Nasional 'Veteran' Jakarta. This study was an observational analytic study with cross-sectional design. This study used 87 students as samples and the Global Physical Activity Questionnaire (GPAQ) to measure physical activity and Food Frequency Questionnaire (FFQ) to measure sodium intake. The data was analyzed through the Kolmogorov-Smirnov test. This study proves that physical activity is significantly correlated with blood pressure (p=0,018) and sodium intake is not correlated with blood pressure (p=0,985) in first-year faculty of medicine students Universitas Pembangunan Nasional 'Veteran' Jakarta.